Collaborative Learning Improves Nursing Students' Knowledge of AED Use in Basic Life Support - Elfi quyumi rahmawati; Nirmala Kusumaningrum Sunaryo; Fresty Africia; Bambang Wiseno (Care : Jurnal Ilmiah Ilmu Kesehatan, 2026)
rescue programs is becoming increasingly widespread, serving as a vital component in the chain of survival for cardiac arrest cases. However, the effectiveness of training programs for rescuers often faces challenges regarding skill acquisition and retention. Collaborative learning has emerged as an educational trend that emphasizes social interaction and shared responsibility within small groups to accomplish tasks or solve problems. The purpose of this study was to determine the effect of collaborative learning in efforts to increase knowledge of AED use in BLS (Basic Life Support). This study employed a pre-experimental, one-group pre-test/post-test design. The study population consisted of 58 nursing students from a vocational college in Kediri, selected via total sampling. The knowledge of Automated External Defibrillators use in Basic Life Support were gathered using a questionnaire and analyzed with the Wilcoxon Signed-Rank Test. The results demonstrated a statistically significant improvement in knowledge levels (p-value = 0.000 0.05), with the mean score increasing from 1.76 in the pre-test to 2.40 in the post-test. Furthermore, the calculated effect size was -0.67 indicating that collaborative learning has a large effect on improving participants knowledge. This study was reported in compliance with the STROBE guidelines. A recommendation for future research is to integrated the collaborative approach with technology-based media, such as video-guided training or interactive CD-ROMs.